Premature newborns and hospital discharge: an integrative review on nursing performance - Kayna Trombini Schmidt; Jacqueline Botura Bessa; Bruna Caroline Rodrigues; Mônica Mauad Arenas; Darci Aparecida Martins Corrêa; Ieda Harumi Higarashi (Rev Rene)
The purpose of this research was to investigate evidence of nursing actions taken towards mothers of premature infants, admitted to neonatal units, in the preparation of hospital discharge and point out difficulties arising from the practice. Seven articles from LILACS, BDENF, MEDLINE and electronic library SCIELO, between 2004 and 2010, were selected. The main nursing actions mentioned were: breastfeeding support; hygiene care; vaccination and milking guidelines; affective bonding encouragement and ambulatory monitoring after discharge. Only three articles have reported difficulties: parents’ interference on the care, relationship problems between families and professionals, and parents’ fears in care performance. A standardization of information provided by health staff in neonatal units seems to be necessary together with the systematization on the family preparation for hospital discharge.